Argentina : Detailed Assessment of Observance of IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2012)
This assessment finds that Argentina has made significant progress to improve its securities regulatory system within the existing legal framework. This assessment finds areas that need to be improved. The reinforcement of supervision powers in accordance to international standards represents an immediate task. The assessment included a review of the main securities laws, executive decrees, and general and trading of securities. The government acknowledges that important challenges remain, and the assessments were noteworthy to identify many of them.